2016
DOI: 10.1080/00207454.2016.1257992
|View full text |Cite
|
Sign up to set email alerts
|

The central cannabinoid receptor type-2 (CB2) and chronic pain

Abstract: Cannabinoid receptor type-2 (CB2, CB2 receptor or CB2-R) mediates analgesia via two mechanisms. CB2 receptors contained in peripheral immune tissue mediate analgesia by altering cytokine profiles, and thus have little adverse effects on central nervous systems (CNSs). CB2 is also expressed in the neurons and glial cells of the CNS. This neuronal expression may also contribute to pain attenuation. The CB2 receptor has been proposed as a potential target in treating chronic pain of several etiologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 112 publications
0
27
0
Order By: Relevance
“…Both CB1 and CB2 receptor agonists demonstrate anti-nociceptive activity, whether used singly or in combination, with CB2 activity believed to affect microglial cells and thereby reduce neuro-inflammatory mechanisms [ 34 , 35 ]. The CB2 receptor is thought to be particularly important in central neuronal pain circuits, as agonist activity induces dopamine release in mid-brain areas, contributing to descending pain control and the placebo effect [ 36 ]. Inflammatory effects can either be modulated via the upregulation of cannabinoid receptor activity or increased production of endocannabinoids, providing an attenuation in joint destruction in preclinical models of inflammatory arthritis that mimic human rheumatoid arthritis [ 30 , 32 ].…”
Section: Role Of Cannabinoids In Inflammation and Painmentioning
confidence: 99%
“…Both CB1 and CB2 receptor agonists demonstrate anti-nociceptive activity, whether used singly or in combination, with CB2 activity believed to affect microglial cells and thereby reduce neuro-inflammatory mechanisms [ 34 , 35 ]. The CB2 receptor is thought to be particularly important in central neuronal pain circuits, as agonist activity induces dopamine release in mid-brain areas, contributing to descending pain control and the placebo effect [ 36 ]. Inflammatory effects can either be modulated via the upregulation of cannabinoid receptor activity or increased production of endocannabinoids, providing an attenuation in joint destruction in preclinical models of inflammatory arthritis that mimic human rheumatoid arthritis [ 30 , 32 ].…”
Section: Role Of Cannabinoids In Inflammation and Painmentioning
confidence: 99%
“…199 CB2 receptor antagonists may be a potential target in treating chronic pain of several etiologies by modifying cytokine profile when blocking peripheral immune tissue receptors, and by blocking receptors in neurons and glial cells. 200 …”
Section: Survey Of Current Targets Of Pain Therapeuticsmentioning
confidence: 99%
“…Cannabinoid CB2 receptor (CB2r) agonists show efficacy in animal models of chronic inflammatory and neuropathic pain, suggesting that they may be effective inhibitors of persistent pain in humans (Bie et al, 2018; Maldonado et al, 2016; Shang and Tang, 2017). However, many preclinical studies assess reflexive-defensive reactions to evoked nociceptive stimuli and fail to take into account spontaneous pain, one of the most prevalent symptoms of chronic pain conditions in humans (Backonja and Stacey, 2004; Mogil et al, 2010; Rice et al, 2018) that triggers coping responses such as painkiller consumption.…”
Section: Introductionmentioning
confidence: 99%
“…CB2r, the main cannabinoid receptors in peripheral immune cells (Fernández-Ruiz et al, 2007; Schmöle et al, 2015a), are found in monocytes, macrophages and lymphocytes, and their expression increases in conditions of active inflammation (Schmöle et al, 2015b; Shang and Tang, 2017). The presence of CB2r in the nervous system was thought to be restricted to microglia and limited to pathological conditions or intense neuronal activity (Manzanares et al, 2018).…”
Section: Introductionmentioning
confidence: 99%